Reliability and Maintenance of Motor Operated Valves, in the Romanian Natural Gas Compression and Distribution Stations - Vlăducă, Iulian; Isac, Robert Andrei; Ringheanu, Vicentiu Liviu; Toma, Emilian; Petre, Carmen; Stanciuc, Ramona-Manuela; Constantin, Daniela; Vasile, Mirela-Letitia (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
The work defines the philosophy of COMOTI – Romanian Research & Development Institute for Gas Turbines, in the predictability of intervention time in case of defects, respectively the reduction of the cost price of maintenance for its MOVs (Motor Operated Valves), used on its own equipments for natural gas compression, existing in the natural gas compression and distribution sites from Romania. In the present work, the emphasis is on operational reliability and mentability, which are capitalized on the basis of the results regarding the operating behavior, over a certain period of time, of a large number of identical types of MOVs, actually used by the beneficiaries.